Case Report Acute febrile illness with skin rash with multiorgan affection presented as scrub typhus: Scrub Typhus (Bombay Hospital Journal, 2026)
Abstract :Aim: To diagnose and treat the patient with acute febrile illness and multiorgan failure affection who presented as scrub typhusBackground: Scrub typhus fever is a disease caused by Orientia TsutsugamushiCase Description: Adult male patient who has gone for picnic at hilly area and who presented after 5 days   with acute febrile illness and deteriorated with skin rash and multi organ affection.  His tropical fever panel investigations were normal and found to have high titre of Weil   Felix test and PCR for rickettsia was positive. He responded well with doxycycline injection and was discharged.Conclusion: Scrub typhus is characterized by skin rash initially maculopapular, progressing to petechial and spreading centripetally in patient with high fever, myalgia, and headache with supportive epidemiologic or exposure history .Classical triad includes Morbilliform eruption plus fever plus necrotic papule (eschar at the tick bite site) should prompt diagnosis of scrub typhus infection.Clinical significance: With prompt diagnosis and identifying the main characteristic features of scrub typhus such as Eschar is important to identify so that the appropriate treatment can be started. Doxycycline is the mainstay treatment
Keywords: Weil Felix Test; Orientia tsutsugamushi; skin rash with Eschar formation